Creative Marketing and Innovative Branding: An Effective Way to Attract Customers - Rahman, Mofasser; Saha, Sajeeb; Anny, Sauda Afrin; Afrin, Sharmin; Afrin, Tanjina; Haq, Iqramul (The Economics and Finance Letters, 2020)
Recently, the demand and application of creative marketing and innovative branding have been increased surprisingly because of its ability to grab the attention of customers more quickly than any other media. The objective of this study is to investigate the dimension of effectiveness in creative marketing and innovative branding to attract customer in the tourism and hospitality industry of Bangladesh. Purposive sampling was applied to take a sample of 150 including 117 customers and 33 service providers of the tourism and hospitality industry of Bangladesh. Descriptive analysis, chi-square goodness of fit, chi-square test of independence, and binary logistic regression were performed to obtain the purpose of the study. In the bivariate test (chi-square test of independence) all of creative marketing and innovative branding strategies and tools were found significantly effective to attract customers in that specific industry. But binary logistic regression analysis identified only launching mobile apps and promoting Bangladesh’s tourism is significant for customer attraction in the tourism and hospitality industry of Bangladesh among different creative marketing and innovative branding strategies and tools. Bangladesh tourism and hospitality industry should practice creative marketing and innovative branding tools and strategies to attract more customers.